2009
DOI: 10.1152/ajplung.00151.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract induces COX-2 expression via a PKCα/c-Src/EGFR, PDGFR/PI3K/Akt/NF-κB pathway and p300 in tracheal smooth muscle cells

Abstract: Exposure to cigarette smoke extract (CSE) leads to airway or lung inflammation, which may be mediated through cyclooxygenase-2 (COX-2) expression and its product prostaglandin E2 (PGE2) synthesis. The aim of this study was to investigate the molecular mechanisms underlying CSE-induced COX-2 expression in human tracheal smooth muscle cells (HTSMCs). Here, we describe that COX-2 induction is dependent on PKCalpha/c-Src/EGFR, PDGFR/PI3K/Akt/NF-kappaB signaling in HTSMCs. CSE stimulated the phosphorylation of c-Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 60 publications
(76 reference statements)
8
42
2
1
Order By: Relevance
“…Although c-Src is typically viewed as a downstream target of EGFR, cSrc was required for the tyrosine phosphorylation and hence activation of EGFR in CSE-treated SAE cells. This study and others have shown that cigarette smoke phosphorylates c-Src via a PKCa-dependent mechanism (9,29). Once activated by cigarette smoke, c-Src phosphorylated EGFR and KRAS/Raf, and these signaling proteins further activated cSrc.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Although c-Src is typically viewed as a downstream target of EGFR, cSrc was required for the tyrosine phosphorylation and hence activation of EGFR in CSE-treated SAE cells. This study and others have shown that cigarette smoke phosphorylates c-Src via a PKCa-dependent mechanism (9,29). Once activated by cigarette smoke, c-Src phosphorylated EGFR and KRAS/Raf, and these signaling proteins further activated cSrc.…”
Section: Discussionsupporting
confidence: 57%
“…In fact, studies indicate that CSE can stimulate the phosphorylation of c-Src, EGFR, PDGFR, and Akt in a PKC-a-dependent manner (9). For this reason, we examined how PKC-a silencing affected c-Src-mediated inflammation in SAE cells.…”
Section: Silencing Of Pkc-a Subdues the Cigarette Smoke-driven Csrc Pmentioning
confidence: 97%
See 1 more Smart Citation
“…MiR-155-mediated repression of SHIP1 led to enhanced activation of the phosphoinositide-3-kinase (PI3K)/AKT pathway in IB3-1 cells. In hASMCs, the PI3K/AKT pathway was observed to partly mediate cigarette smoke extract induction of COX-2 in hASMCs (47). Furthermore, AKT was previously observed to enhance the stability of COX-2 mRNA in rat intestinal epithelial cells (48).…”
Section: Resultsmentioning
confidence: 79%
“…Sigara dumanının, inflamasyon mekanizmalarında önemli rolleri olan siklooksijenaz-2 ve fosfolipaz A2 enzimini arttırdığı diğer çalışmalarda gösterilmiştir (23)(24). Bizim çalışmamızda da benzer şekilde sigara dumanı siklooksijenaz-2, Fosfolipaz A2 ve iNOS enzimlerinin miktarında artışa neden olurken antiinflamatuar özelliği gösterilen alfalinolenik asit bu artışları anlamlı olarak azalttı.…”
Section: Discussionunclassified